African literature and social change : tribe, nation, race - George, Olakunle (Indiana University Press, 2017)
Alert to the ways in which critical theory and imaginative literature can enrich each other, African Literature and Social Change reframes the ongoing project of African literature. Concentrating on texts that are not usually considered together--writings by little-known black missionaries, so called "black whitemen," and better-known 20th century intellectuals and creative writers--Olakunle George shows the ways in which these writings have addressed notions of ethnicity, nation, and race and how the debates need to be rehistoricized today. George presents Africa as a site of complex desires and contradictions, refashioning the way African literature is positioned within current discussions of globalism, diaspora, and postcolonialism.